Penyuluhan Hukum Tentang Pencegahan Anti Bullying Bagi Siswa-Siswi SD N 1 Di Desa Podoluhur Kecamatan Klirong Kabupaten Kebumen - Wiyono, Wiwin Muchtar (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bullying is an act of physical and verbal violence, where the perpetrator humiliates and intimidates the victim so that they cannot fight back. The perpetrator of the bullying seeks pleasure that he cannot get and takes it out by making other people suffer. The impact of bullying will hinder children from actualizing themselves because bullying behavior will not provide a sense of security and comfort, and will make victims of bullying feel afraid and intimidated, low self-esteem, worthless, difficult to concentrate on studying, and unable to socialize with their environment. The purpose of this community service is to find out efforts to prevent bullying against students at SD Negeri 1 Podoluhur Village, Klirong District, Kebumen Regency in terms of Positive Law. If someone commits an act that violates the law, then punishment can be imposed on the perpetrator of the crime. The perpetrator may be punished with any punishment, as long as with this punishment the punisher's goal can be achieved, namely to deter the perpetrator and make others afraid of committing criminal acts. So that bullying does not occur, it can be used as an alternative effort to prevent bullying behavior. So it is recommended for every party to prevent bullying by holding outreach activities and seminars that discuss bullying, and putting up banners in every corner of the school so that students remember that bullying is not justified. Keywords: Prevention, Bullying, Legal Protection